Function of Riparian Vegetation in Retaining Sediment in Watersheds - Neary, Daniel G. (Arizona-Nevada Academy of Science, 2010)
From the Proceedings of the 2010 Meetings of the Hydrology Section - Arizona-Nevada Academy of Science - April 10, 2010, Northern Arizona University, Flagstaff, Arizona